2012
DOI: 10.1016/j.neuron.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Cognitive Training Restores Neural Activity within the Reality Monitoring Network in Schizophrenia

Abstract: SUMMARY Schizophrenia patients suffer from severe cognitive deficits, such as impaired reality monitoring. Reality monitoring is the ability to distinguish the source of internal experiences from outside reality. During reality monitoring tasks, schizophrenia patients make errors identifying “I made it up” items, and even during accurate performance, they show abnormally low activation of the medial prefrontal cortex (mPFC), a region that supports self-referential cognition. We administered 80 hours of compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
287
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(318 citation statements)
references
References 58 publications
26
287
1
2
Order By: Relevance
“…We found that the schizophrenia participants who received the targeted training showed behavioral improvements on (untrained) neuropsychological measures of verbal memory and on reality-monitoring tasks, thus indicating generalization of training effects. Further, after the intervention, neural activation patterns during reality monitoring, which were abnormal in these patients at baseline, began to resemble the patterns observed in healthy participants (Figures 1a and c), and predicted better social functioning 6 months later (Subramaniam et al, 2012).…”
Section: Cognitive Training For Psychiatric Disordersmentioning
confidence: 58%
See 2 more Smart Citations
“…We found that the schizophrenia participants who received the targeted training showed behavioral improvements on (untrained) neuropsychological measures of verbal memory and on reality-monitoring tasks, thus indicating generalization of training effects. Further, after the intervention, neural activation patterns during reality monitoring, which were abnormal in these patients at baseline, began to resemble the patterns observed in healthy participants (Figures 1a and c), and predicted better social functioning 6 months later (Subramaniam et al, 2012).…”
Section: Cognitive Training For Psychiatric Disordersmentioning
confidence: 58%
“…Increasing evidence indicates that these neural system dysfunctions are not immutably fixed, but instead may be amenable to well-designed cognitive training interventions that target restoration of neural system operations (Browning et al, 2012;Klingberg et al, 2005;Subramaniam et al, 2012). An explicitly 'systems neuroplasticity'-based approach to cognitive training is founded on the premise that during successful skill learning, disproportionately larger and better-coordinated neuronal populations represent the salient inputs and action outputs of the trained skill, resulting in an increased feed-forward signal strength from sensory regions as well as greater task-relevant feedback-inhibitory control from the prefrontal cortex to enhance representations of relevant stimuli, and to enable more efficient and accurate associative memory processes .…”
Section: Cognitive Training For Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study published last week showed that intensive training can improve people's performance in a task that assesses the ability to distinguish what is real from what is not. Those who improved most had significantly enhanced social functioning six months later 6 . When combined with other interventions, such as counselling and job-placement programmes, as the current trial at Citywide clinic is, cognitive remediation approaches seem to help patients function better in society -for instance, by helping them to keep jobs 7 .…”
Section: Train Of Thoughtmentioning
confidence: 96%
“…Improvements have been noted not just in cognitive functions that the training methods targeted, but also in cognitive domains that were not directly targeted as well as measures of global cognitive abilities. Not surprisingly, the response to cognitive training response is associated with structural and functional changes in prefrontal area of the brain [10,11]. The gains of cognitive training are likely to be durable for several months beyond the training period [12,13].…”
Section: Cognitive Training In Schizophreniamentioning
confidence: 99%